2020
DOI: 10.1038/s41598-020-76845-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal blood lipids levels during pregnancy and risk of small-for-gestational-age infants

Abstract: Dyslipidemia in pregnancy are associated with risk of adverse outcomes. As an adverse pregnancy outcome, small-for-gestational-age has been extensively studied in Western countries. However, similar studies have rarely been conducted in Asian countries. Data were derived from 5695 pairs of non-diabetic mothers and neonates between 1 Jan 2014 and 31 Dec 2014. 5.6% neonates in our study were SGA. Serum samples were collected during second and third trimesters for evaluation on fasting lipids levels. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Four of these included publications were cohort studies ( 12 14 , 17 ), two were case-control studies ( 15 , 18 ) and two were cross-sectional studies ( 11 , 16 ). They were conducted in different countries, Netherlands ( 12 ), China ( 13 ), Turkey ( 16 ), Japan ( 18 ), Korea ( 14 ), Canada ( 15 ), German ( 17 ) and Egypt ( 11 ) separately. Among the selected studies, three reported maternal lipid profile during early pregnancy ( 12 , 14 , 16 ), three during mid-pregnancy ( 15 , 17 , 18 ), and one during mid and late pregnancy ( 13 ) in detail, yet one study didn’t mention this information ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of these included publications were cohort studies ( 12 14 , 17 ), two were case-control studies ( 15 , 18 ) and two were cross-sectional studies ( 11 , 16 ). They were conducted in different countries, Netherlands ( 12 ), China ( 13 ), Turkey ( 16 ), Japan ( 18 ), Korea ( 14 ), Canada ( 15 ), German ( 17 ) and Egypt ( 11 ) separately. Among the selected studies, three reported maternal lipid profile during early pregnancy ( 12 , 14 , 16 ), three during mid-pregnancy ( 15 , 17 , 18 ), and one during mid and late pregnancy ( 13 ) in detail, yet one study didn’t mention this information ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well-established that SGA is associated with low pre-pregnancy body mass index (5), sleep disturbances (6), short stature (7), serum plasma protein A levels (8), smoking (9) and maternal antioxidant levels (10). Recently, gestational dyslipidemia has also been reported to be a risk factor for SGA infant delivery (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, low prepregnancy cholesterol may be a marker of poor nutritional status or a baseline inflammatory state that leads to PTB-inducing cascade, whereas high prepregnancy cholesterol represents a “proatherogenic phenotype” with increased risk of PTB. 35 …”
Section: Management Of Chronic Hypertension During Pregnancymentioning
confidence: 99%
“…However, no correlations were observed between low-density lipoprotein cholesterol (LDL-C) or total cholesterol (TC) levels and adverse neonatal pregnancy outcomes ( 13 ). Another study in China showed that TC levels during the third trimester of pregnancy were associated with a lower risk of SGA, whereas HDL-C and LDL-C levels during late pregnancy were associated with an increased risk of SGA ( 14 ). Several studies have shown that in well-controlled GDM, maternal TG concentration is positively correlated with newborn fat mass and LGA ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%